Kinetic mechanism and equilibrium thermodynamic of lipase catalyzed synthesis of rutin flavonoid ester / Nurul Nadiah Abd Razak - Nurul Nadiah , Abd Razak (2015)
Flavonoids are natural compounds in plant with wide spectrum of healthbeneficial activities. They exhibit a variety of physico-chemical properties and biological activities but they are normally characterized by low solubility and stability. In order to improve upon these limitations, the enzymatic acylation of these molecules with fatty acids is seen as a selective, specific and mild route. In this study, the synthesis of flavonoid esters catalyzed by lipase was investigated. Three different flavonoid structures from different classes were selected to be studied viz. rutin (flavonols), naringin (flavanones) and catechin (flavanols). The effects of these flavonoid structures on the esterification were investigated with lauric acid as an acyl donor. The results showed that rutin was the most reactive substrate. Conversion yields were at 56 % and 47 % for rutin and naringin, respectively. For an aglycone flavonoid, such as catechin, no glycoside ester formation was observed. Based on the conversion yield and solubility consideration, rutin was selected for further studies. For different chain length fatty acid (C12–C16), no significant difference was observed in terms of yield irrespective of fatty acids used. Full factorial experimental design (FFD) was used to study the effects of different process parameters towards the synthesis of rutin laurate. The effects of three selected operating variables viz. lauric acid concentration (M), temperature (ºC) and enzyme loading (g) were significant in all cases (P < 0.05). The factors studied showed temperature has the strongest influence on the ester yield followed by lauric acid concentration and enzyme loading. In thermo-kinetic investigation, analysis indicated that lipase-mediated esterification exhibited Ping-Pong Bi-Bi mechanism with no apparent inhibition by both substrates. The apparent kinetic of the esterification reaction followed a first-order behavior. The magnitude of glycoside ester formation and the apparent first-order rate constant, k1’ value increased with temperature. Activation energy, Ea for the esterification was calculated at 37 kJ mol−1. The esterification process was endothermic with the enthalpy, H and entropy, S values calculated at +51 kJ mol-1 and +113 J mol-1 K-1, respectively. Based on the value of Gibbs free energy change, G the esterification reaction under the conditions studied was predicted to be non-spontaneous below 175 °C but spontaneous at higher temperatures. The study also confirmed, through 13C-NMR analysis, the exact location of rutin esterification. The investigated process biochemistry highlighted important behavior concerning the biosynthesis of functionalized flavonoid with implication for reactor design.behavior. The magnitude of glycoside ester formation and the apparent first-order rate constant, k1’ value increased with temperature. Activation energy, Ea for the esterification was calculated at 37 kJ mol−1. The esterification process was endothermic with the enthalpy, H and entropy, S values calculated at +51 kJ mol-1 and +113 J mol-1 K-1, respectively. Based on the value of Gibbs free energy change, G the esterification reaction under the conditions studied was predicted to be non-spontaneous below 175 °C but spontaneous at higher temperatures. The study also confirmed, through 13C-NMR analysis, the exact location of rutin esterification. The investigated process biochemistry highlighted important behavior concerning the biosynthesis of functionalized flavonoid with implication for reactor design.